REPRESENTASI GENDER DALAM FILM TELEVISI KISAH NYATA - Handayanti, Asih; Septadinusastra, Vina Alvinia; Rahayu, Asri Sri; Haryadi Mujianto; Neni Yulianita (LPPM Stikosa - AWS, 2024)
The research was conducted on two Real Story FTV titles entitled